The Concept of Humanity from the Perspective of Ibn Sina (Avicenna) - Yusron Yusron; Ekawati (Maklumat: Journal of Da'wah and Islamic Studies, 2025)
This study examines Ibn Sina's concept of humankind, which views humans as a unity of body and soul. Ibn Sina divides the soul into three levels: the vegetable, the hayawani, and the human, with the human soul as the center of consciousness, knowledge, and morality. This concept aligns with Islamic teachings, which emphasize the dignity of humans as creatures infused with a spirit by God and entrusted with the role of caliph on earth. This study uses a library method with a qualitative, descriptive-analytical approach. The results of the study indicate that Ibn Sina's thinking is relevant for the development of holistic education that integrates physical, intellectual, and spiritual aspects, and can be applied in character building, leadership, and social life in the modern era.